Magnetic properties of a LuVO3 single crystal studied by magnetometry, heat capacity and neutron diffraction - L.D. Tung; J. Schefer; M.R. Lees; G. Balakrishnan; D.McK. Paul (Journal of Science: Advanced Materials and Devices, 2016)
We have studied the magnetic properties of a LuVO3 single crystal. The compound shows an orbital ordering at TOO = 179 K followed by the antiferromagnetic spin ordering at TSO = 109 K. In the magnetically ordered regime, there appears an abrupt change at To = 82.5 K in the magnetisation, indicating a first-order transition. The compound has very large negative Weiss temperature observed along all the main crystallographic axes, suggesting a strong antiferromagnetic correlations in the paramagnetic state. The observation of hysteresis curves in the collinear antiferromagnetic regime is discussed in terms of an inhomogeneity generating some spins with weak local fields in a strongly antiferromagnetic matrix.